Komitmen Organisasi dan Kepuasan Kerja Guru di SMA Negeri di Kota Kupang - Delsylia Tresnawaty Ufi; Sutarto Wijono (Universitas Kristen Maranatha, 2020)
This study aims to determine the relationship between dimensions of organizational commitment and job satisfaction in State Senior High School teachers in Kupang. Using the proportionate random sampling technique, we obtained 106 certified teachers. The teacher filled out the Organizational Commitment Scale, which consists of 30 items that measure organizational commitment, including affective, continuance, and normative commitment, and the Overall Job Satisfaction scale. Through correlation analysis, the research results show that there is a significant relationship between the three dimensions of organizational commitment (affective commitment, continuance commitment, and normative commitment) with job satisfaction (p <0.05). Keywords: Organizational commitment, affective commitment, continuance commitment, normative commitment, job satisfaction